Use of dexmedetomidine as adjunctive therapy for anti-N-methyl-D-aspartate receptor encephalitis - Babbitt, Christopher J.; Lake, Jean; Levine, Glenn K. (Journal of Pediatric Intensive Care, 2013)
Anti-N-methyl-D-aspartate receptor encephalitis is a recently discovered disease that is more commonly being diagnosed in children. Patients often require intensive care and assisted ventilation due to agitation, abnormal movements, hypoventilation, seizures and autonomic instability. There is no consensus on which medicines are best suited to acutely treat this constellation of central nervous system symptoms. We present the first case report of using dexmedetomidine to treat this condition.
Keywords: Dexmedetomidine; encephalitis; seizures; anti-N-methyl-D-aspartate receptor